THE IMPORTANCE OF DEVELOPING EMOTIONAL INTELLIGENCE IN THE EDUCATION SYSTEM (Universal International Scientific Journal, 2026)
This article analyzes the importance of developing the emotional intelligence (EQ)of pupils and students in the modern education system and explores advanced technologies in thisfield. The research highlights interactive methods and psychological approaches aimed at managingemotions, developing empathy, and building social skills. Furthermore, the impact of emotionalintelligence on academic achievement and personal success is substantiated throught internationalexperiences.
Keywords: Emotional intelligence (EQ); empathy; social-emotional learning (SEL)